Winning with difficult people understanding behavior - HSTN; Primedia Workplace Learning (Carrollton, Tx : Primedia Healthcare, 2003)
Discusses a strategy to understand difficult behavior and what may or may not cause it; gives examples of the six options available in responding to a difficult person
VHS format
Keywords: Interpersonal relations; Social behavior; Attitude